Insights into the protective role of solid lipid nanoparticles on rosmarinic acid bioactivity during exposure to simulated gastrointestinal conditions - Madureira, Ana Raquel (2017)
The evaluation of the digestion effects on bioactive solid lipid nanoparticles (SLN) was performed. For this purpose, witepsol and carnauba SLN loaded with rosmarinic acid (RA) were exposed to the simulated gastrointestinal tract (GIT) conditions prevailing in stomach and small intestine. The simulation of intestinal epithelium was made with a dialysis bag and intestinal cell culture lines. Changes on SLN physical properties, RA release and absorption profiles were followed at each step. Combination of digestion pH and enzymes showed a significant effect upon SLN physical properties. Zeta potential values increased at stomach conditions and decreased at small intestine simulation. Also, at intestine, SLN increased their sizes and released 40-60% of RA, maintaining its initial antioxidant activity values. Sustained release of 40% of RA from SLN was also observed in dialysis tube. At CaCo-2 cell line, both types of SLN showed similar absorbed RA % (ca. 30%). Nevertheless, in CaCo-2/HT29x mix cell lines, for carnauba SLN a lower adsorption RA % was observed than for witepsol SLN. Solid lipid nanoparticles protected RA bioactivity (in terms of antioxidant activity) until reaching the intestine. A controlled release of RA from SLN was achieved and a significant absorption was observed at intestinal cells. Overall, SLN produced with witepsol showed a higher stability than carnauba SLN.